2008
DOI: 10.2527/jas.2007-0475
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen recycling through the gut and the nitrogen economy of ruminants: An asynchronous symbiosis1

Abstract: The extensive development of the ruminant forestomach sets apart their N economy from that of nonruminants in a number of respects. Extensive pregastric fermentation alters the profile of protein reaching the small intestine, largely through the transformation of nitrogenous compounds into microbial protein. This process is fueled primarily by carbohydrate fermentation and includes extensive recycling of N between the body and gut lumen pools. Nitrogen recycling occurs via blood and gut lumen exchanges of urea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
239
1
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 327 publications
(262 citation statements)
references
References 63 publications
(121 reference statements)
16
239
1
6
Order By: Relevance
“…The linear regression between N intake and UER showed that net urea N release by the liver accounted for 71.5% of N intake in cattle. The slope estimate was close to those reported by Reynolds and Kristensen (2008), which was 72% for growing cattle and 60.2% for dairy cows. However, the intercept of the linear regression observed by these authors was significant, whereas in this current meta-analytical approach it was not significant.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The linear regression between N intake and UER showed that net urea N release by the liver accounted for 71.5% of N intake in cattle. The slope estimate was close to those reported by Reynolds and Kristensen (2008), which was 72% for growing cattle and 60.2% for dairy cows. However, the intercept of the linear regression observed by these authors was significant, whereas in this current meta-analytical approach it was not significant.…”
Section: Discussionsupporting
confidence: 89%
“…This seems to indicate that when dietary CP is >17%, the excess of N intake decreases the efficiency of renal urea reabsorption and therefore decreases the efficiency of urea N recycling, with a resulting increase in the amount of urinary urea N excreted. These results emphasize the inherent ability of ruminants to salvage urea N for recycling and subsequent anabolic purposes when dietary protein is limited (Reynolds and Kristensen, 2008).…”
mentioning
confidence: 57%
See 2 more Smart Citations
“…Nutrient transport In addition to SCFA, transport of nutrients such as urea is of particular importance to ruminant nutrition and physiology as the availability of nitrogen and amino acid supply for ruminants is greatly influenced by microbial metabolism of urea in the rumen (Reynolds and Kristensen, 2008). Therefore, knowledge of mechanisms that regulate its supply to the rumen could be used to improve nitrogen balance in production animals.…”
Section: Introductionmentioning
confidence: 99%